2013
DOI: 10.1063/1.4772950
|View full text |Cite
|
Sign up to set email alerts
|

Emission enhancement mechanism of GaN:Eu by Mg codoping

Abstract: Mg codoping into Eu-doped GaN strongly affects the two dominant optical sites A (620.3 nm) and B (622.3 nm) and dramatically improves the optical characteristics obtained from Eu 3þ ions. To clarify the mechanism of the enhanced emission, the effects of the Mg concentration on the excitation and emission processes were evaluated by considering the excitation power dependence of photoluminescence (PL) and time-resolved PL at various temperatures. The excitation cross section r ex , which reflected the excitatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
7
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 28 publications
(26 reference statements)
5
7
0
Order By: Relevance
“…The excitation cross section did not depend on N Mg , for any of the optical sites (not shown), indicating that Mg codoping did not influence excitation efficiency. The excitation cross section for site A was larger than that for site B, which is in good agreement with other reports on GaN:Eu fabricated by ion implantation and GaN: (Eu, Mg) grown by MBE [20,25].…”
Section: Effect Of Mg Codoping On Optical Properties Of Eu-doped Algansupporting
confidence: 93%
See 2 more Smart Citations
“…The excitation cross section did not depend on N Mg , for any of the optical sites (not shown), indicating that Mg codoping did not influence excitation efficiency. The excitation cross section for site A was larger than that for site B, which is in good agreement with other reports on GaN:Eu fabricated by ion implantation and GaN: (Eu, Mg) grown by MBE [20,25].…”
Section: Effect Of Mg Codoping On Optical Properties Of Eu-doped Algansupporting
confidence: 93%
“…The PL decay time at RT increased from 51 to 164 μs with increasing N Mg , which suggested that Mg codoping was effective to reduce the nonradiative component resulting from the backtransfer process; that is, Mg codoping might contribute to decrease the native or unwanted defect in the AlGaN host as well as GaN [25].…”
Section: Effect Of Mg Codoping On Optical Properties Of Eu-doped Alganmentioning
confidence: 96%
See 1 more Smart Citation
“…First, to understand the effect of Eu concentration on the transfer efficiency, σ ex at 25 K as a function of Eu concentration is shown in Figure . σ ex was almost constant at 1 × 10 −16 –4 × 10 −16 cm 2 , which is consistent with that of GaN:Eu thin film fabricated by ion implantation or grown by RF‐MBE in previous reports, even at a concentration higher than that at which concentration quenching was observed. This indicated that the transfer efficiency from GaN to Eu ion was not affected by the Eu concentration.…”
Section: Growth Of Self‐organized Gan:eu Nanocolumnssupporting
confidence: 91%
“…[1][2][3][4] While the optical and magneto-optical properties of this system have been extensively studied, information on the nature and structure of the incorporation environments of Eu in GaN is still incomplete. [5][6][7][8][9][10][11][12][13][14][15][16][17][18] In early samples, as many as eight incorporation sites have been identified in GaN:Eu, grown by organometallic vapor-phase epitaxy (OMVPE). 17 However, it has been determined that two of these sites, commonly referred to as Eu1 and Eu2, represent roughly 85-95% of the overall Eu incorporation in GaN, and play the largest role in the luminescence properties of the system.…”
Section: Introductionmentioning
confidence: 99%